Pseudo-Ptosis. Issue 6 (1st December 2002) - Stone, Jon
Abstract : This 52-year-old man slipped on a wet floor at work and was briefly 'knocked out', sustaining a bruise to his left temple. Over the next week or so he was off work with headaches and dizziness. When he returned to his desk he found that the light from his computer screen was hurting his left eye. He was referred because of 'ptosis' and photophobia. In fact, he had normal levator function of his eyelid, the appearance being entirely due to apparent weakness of left frontalis and contraction of orbicularis (see Fig. 1). The rest of his neurological and ocular examination was normal. With encouragement he was able to activate his left frontalis transiently, but normally. With his eyes shut he was comfortably able to maintain bilateral frontalis elevation (see Figs 2 and 3), indicating that photophobia was playing a significant role in the appearance. Investigations including MRI brain, facial nerve